الصناعة التقليدية كمصدر لترقية السياحة والإستثمار السياحي منطقة أهقار نموذجا - سويتم، فاطمة Suwaitem, Fatemah (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2018)
The economic structure of the state consists of several sectors affected by changes in the economic variables. The tourism sector is an integral part of the national economy and has an effective role in the formation of national output. and Tourism investment is one of these economic structures of the state, and activities promising for the great opportunities for success and financial returns. We concluded that the development of tourism investment depends on the extent of the flow of domestic and foreign capital, to invest in the field of tourism as well as the strength of the tourist product offered and the volume of demand in the tourist market. The tourism sector is based on a number of tourism components Or the qualifications that make it an area for investment and development, especially in the desert areas of Algeria, Among the most important qualification of traditional industries that distinguish each region from other regions. We also found that tourism and traditional industry have economic, social and cultural importance ... and others, as they are a complex industry and intertwined with several elements of nature, human and civilization closely linked with their social and economic environment.
يتكون الهيكل الاقتصادي للدولة من عدة قطاعات تتأثر بالتغيرات التي تطرأ على المتغيرات الاقتصادية، والقطاع السياحي جزء لا يتجزأ من الاقتصاد الوطني وله دور فعال في تكوين الناتج الوطني ويعتبر الاستثمار السياحي أحد هذه الهياكل الاقتصادية للدولة ومن الأنشطة الواعدة لما تتيحه من فرص كبيرة للنجاح وتحقيق عوائد مالية معتبرة، كما نستخلص أن تطور الاستثمار السياحي يتوقف على مدى تدفق رؤوس الأموال المحلية والأجنبية، للاستثمار في مجال السياحة إلى جانب قوة المنتج السياحي المعروض وحجم الطلب عليه في السوق السياحية، ويرتكز القطاع السياحي على جملة من المقومات السياحية أو المؤهلات التي تجعله منه مجال للاستثمار والتنمية وخاصة في المناطق الصحراوية للجزائر، ومن أهم هاته المقومات الصناعات التقليدية التي تميز كل منطقة عن غيرها من المناطق. كما وجدنا أن لكل من السياحة والصناعة التقليدية أهمية اقتصادية واجتماعية وثقافية.. .وغيرها وذلك باعتبار أنهما صناعة مركبة ومتداخلة مع عدة عناصر طبيعة وبشرية وحضارية ترتبط ارتباطا وثيقا مع محيطها الاجتماعي والاقتصادي.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- التنمية المستدامة -- الإستثمار السياحي -- الانشطة السياحية -- المؤسسات السياحية -- الإرشاد السياحي -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث -- الترجمة